(untitled) (Estudos em Design, 2015)
Ergonomics in Built Environment - EBE is a segment of Ergonomics magnifying her look to the environment and objects, taking into consideration the user and his/her tasks. In this paper we will present some relevant definitions and principles to this segment. Such concepts are necessary to the understanding of the main methodologies used in EBE research in Brazil, which will be described here. The checks carried out on the methods used in EBE, will serve as a contribution to an attempt to build a schematic modelling that includes phases of the project in Interior Design, considering methodological aspects of the Built Environment Ergonomics.